Stability of Markovian jump stochastic parabolic Itô equations with generally uncertain transition rates - Zhang, Caihong; Kao, Yonggui; Kao, Binghua; Zhang, Tiezhu (Applied mathematics and computation, 2018)
In this paper, the stability problem for delayed Markovian jump stochastic parabolic Ito^ equations (DMJSPIEs) subject to generally uncertain transition rates (GUTRs) is investigated via Lyapunov-Krasovskii functional and linear matrix inequality (LMI) method. In the model discussed, we suppose that only part of the transition rates of the jumping process are known, namely, some factors have been already available, some elements have been simply known with lower and upper bounds, and the rest of elements may have no useful information. Lastly, the applicability and effectiveness of the obtained results are illustrated through an example.